The Level of Knowledge of Pregnant Women About the MCH Book and ITS Relationship with Antenatal Visits at The Kopo Health Center, Bandung Regency in 2023 - Salma Nurazizah Amatillah (Publikasi Indonesia, 2024)
Improving public health, especially for pregnant women and infants, is a priority in reducing maternal and infant mortality rates. One of the efforts is the use of the Mother and Child Health Book (KIA) as a source of information. However, many pregnant women do not fully understand the content of the KIA book and are not compliant with antenatal visits. The aim of this research is to assess the level of pregnant women's knowledge about the KIA book and its relationship with antenatal visits at the Kopo Community Health Center. This research utilizes a descriptive analytical method with a cross-sectional design. The research sample includes all pregnant women at the Kopo Community Health Center who meet the inclusion criteria, totaling 76 pregnant women. The research findings indicate that pregnant women's knowledge about the Mother and Child Health Book (KIA) has a significant correlation with their compliance with antenatal visits at the Kopo Community Health Center. This suggests that pregnant women with good knowledge of the KIA book are more likely to have regular antenatal visits during their pregnancy, whereas those with lower knowledge levels tend to have fewer antenatal visits.